Combating Corruption with the Measures of Criminal Law - Michailovič, Ilona (Sociologija. Mintis ir veiksmas, 2007)
The article provides an analysis of the issues relating to corruption problems – the social conditionality of corruption, the definition of this phenomenon, and types of corruption. The problems relating to the definition of corruption are analyzed through the prism of criminal law, with the provision of a list of criminal offences and account taken of the requirements of international instruments. Corruption is analyzed as a social problem, while exploring the causes of this phenomenon. It is stated in the article that corruption is still more becoming a modern topic, the causes of this phenomenon may be explained by the provisions of various theories. The term of corruption does not coincide with the terms used for bribery and bribe. Bribery means separate cases that consist of bribe giving, receiving or soliciting, whereas corruption means the condition related to those phenomena, which is negatively assessed in a certain environment or the entire society. The limits of the term of corruption encompass the whole syndrome of this phenomenon. Therefore for efficient prevention of corruption the complex of civil, financial, banking, tax, customs, inheritance, housing, trade, family, ecological, etc. legal norms and only then administrative, criminal proceedings, and criminal law is necessary. However, in terms of human rights the criminal law should be one of the most important guarantees against the criminal encroaching on them and against self-will of the state authorities and officials. Criminal offences of corruptive nature are divided into corruptive criminal offences sensu stricto and sensu largo. Corruptive criminal offences sensu largo are committed committing corruptive criminal offences sensu stricto. A close interaction exists between them in respect of the subject and object, since in many cases a bribe may be a stimulus to another crime, encouragement, reason. Taking into account the provisions of international instruments, corruptive criminal offences sensu stricto would include taking of a bribe (passive corruption), giving of a bribe (active corruption), intermediary bribery (trade in influence) as well as criminal offences of corruptive nature in the private sector. Corruptive criminal offences sensu largo would include, for example, abuse, registration of illicit rights to the item, disclosure of the state secret, disclosure of the secret of office, abuse of power, criminal offences in the field of political corruption, disclosure of commercial secret, etc. This list is incomplete, taking into consideration the complicated nature of corruptive crimes. In terms of corruption prevention it is necessary to stress that social legal control of corruptive activity is not possible without the active cooperation of state anticorruption structures and the civil society. It is possible to seek for formation of the anticorruptive opinion of the society, the role of which is, though slowly, increasing. Therefore it is necessary to prepare the ways and measures.